Third-party peacemakers in Judaism text, theory, and practice - Roth, Daniel 1975- (Oxford University Press, 2021)
"Third-Party Peacemakers in Judaism presents thirty-six case studies featuring third-party peacemakers found within Jewish rabbinic literature. Each case study is explored through three layers of analysis: text, theory, and practice. The textual analysis consists of close literary and historical readings of legends and historical accounts as found within classical, medieval, and early-modern rabbinic literature, many of which are critically analyzed here for the first time. The theoretical analysis consists of analyzing the models of third-party peacemaking imbedded within the various cases studies by comparing them with other cultural and religious models of third-party peacemaking and conflict resolution, in particular the Arab-Islamic sulha and contemporary Interactive Problem-Solving Workshops. The final layer of analysis, based upon the author's personal experiences in years of dong conflict resolution education, trainings, and actual third-party religious peacemaking in the context of the Israeli-Palestinian Conflict, relates to the potential practical implications of these case studies to serve as indigenous models and sources of inspiration for third-party mediation and peacemaking in both interpersonal and intergroup conflicts today"--
Keywords: Geschichte; Rabbinische Literatur; Friedensvermittlung; Konfliktvermeidung; Conflict management / Religious aspects / Judaism; Mediation / Religious aspects / Judaism; Peace in rabbinical literature; Jewish ethics